ULK1 inhibition overcomes compromised antigen presentation and restores antitumor immunity in LKB1-mutant lung cancer - Deng, Jiehui; Thennavan, Aatish; Dolgalev, Igor; Chen, Ting; Li, Jie; Marzio, Antonio; Poirier, John T.; Peng, David H.; Bulatovic, Mirna; Mukhopadhyay, Subhadip; Silver, Heather; Papadopoulos, Eleni; et al. (Nature cancer, 2021)
Inactivating mutations in LKB1/STK11 are present in roughly 20% of nonsmall cell lung cancers (NSCLC) and portend poor response to anti-PD-1 immunotherapy. Unexpectedly, we found that LKB1 deficiency correlated with elevated tumor mutational burden (TMB) in NSCLCs from nonsmokers and genetically engineered mouse models, despite the frequent association between high-TMB and anti-PD-1 treatment efficacy. However, LKB1 deficiency also suppressed antigen processing and presentation, which are associated with compromised immunoproteasome activity and increased autophagic flux. Immunoproteasome activity and antigen presentation were restored by inhibiting autophagy through targeting the ATG1/ULK1 pathway. Accordingly, ULK1 inhibition synergized with PD-1 antibody blockade, provoking effector T-cell expansion and tumor regression in Lkb1-mutant tumor models. This study reveals an interplay between the immunoproteasome and autophagic catabolism in antigen processing and immune recognition, and proposes the therapeutic potential of dual ULK1 and PD-1 inhibition in LKB1-mutant NSCLC as a strategy to enhance antigen presentation and to promote antitumor immunity.Wong and colleagues show that LKB1-deficient lung tumors are sensitive to autophagy inhibition, which can restore impaired antigen presentation and antitumor immune responses, and propose dual targeting of ULK1 and PD-1 for these tumors.